Localized Electroless Deposition of Gold Nanoparticles Using Scanning Electrochemical Microscopy. - Malel, E.; Mandler, D (J. Electrochem. Soc.Journal of the Electrochemical Society, 2008)
The aim of this study is to locally deposit nanoparticles on an unbiased surface by electroless deposition (ED) using scanning electrochem. microscopy (SECM). We have developed an ED process that is based on the redn. of gold ions by hydroquinone (H2Q) and catalyzed by a metallic surface, such as palladium. One of the advantages of this system is the ability to drive the ED at pH 1-7. The metal ions were electrogenerated in a soln. consisting of H2Q and KCl by anodic dissoln. of a gold microelectrode. AuCl4- reacted with H2Q at the electrolyte/metallic interface to form benzoquinone and gold deposit. The ED was studied initially in bulk soln. contg. KCl, H2Q, and HAuCl4, and then by SECM. We found that the pH had a significant effect on the nature of the deposited gold and could be correlated with the kinetics of gold ions redn. by H2Q. Hence, either nanoparticles or much larger crystals could be formed, depending on the pH of the deposition soln. Time of deposition and H2Q concn. also affected the shape and d. of the deposition. [on SciFinder(R)]
CAPLUS AN 2008:546181(Journal)
Keywords: gold nanoparticle hydroquinone redn electroless deposition scanning electrochem microscopy